(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
In this paper, the digital divide in the telecommunication services between 28 member states of the European Union in the period from 2007 to 2011 has been analysed using methods of knowledge discovery in databases. A brief history of telecommunications and essential telecommunication services has been presented, as well as their characteristics. Data related to the indicators of the digital divide in the telecommunication services has been collected and subjected to descriptive analysis. After choosing an optimal set of variables and a method, cluster analysis has been performed for each of the five years of the study period. Groups of EU member states at a similar stage of development of telecommunications have been identified and the characteristics of each of the groups have been described. Additionally, the paper presents some conclusions about changes in the scale of the digital divide in the telecommunications services between EU countries during the study period. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.